Pengaruh Gaya Hidup dan Kelompok Referensi terhadap Keputusan Pembelian Macbook di Universitas 17 Agustus 1945 Surabaya - Indira Sarah Rachmawati; Diana Juni Mulyati; Agung Pujianto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The development of digital technology has brought major changes in various aspects of human life, especially in the fields of education and the world of work. In this modern era, laptops have become one of the essential devices, especially for students who also work. Laptops are not only used to complete academic assignments, but also to support professional work and daily social activities. One of the most popular laptop brands is the Apple MacBook, which is known for its elegant design, high performance, long battery life, and excellence in integration between devices through the Apple ecosystem. In the environment of the University of 17 August 1945 Surabaya, MacBooks are increasingly popular among working students because they are considered devices that support high productivity and are valuable long-term investments. This study aims to analyze the influence of lifestyle and reference groups on the decision to purchase Apple laptops (Macbook) among working students. The research method used is a quantitative approach by distributing questionnaires online via Google Form. The sampling technique applied is convenience sampling, with a total of 90 respondents who are active students who also work. Data were analyzed using multiple linear regression. The results of the study indicate that simultaneously Lifestyle and Reference Groups have a positive and significant effect on the Purchase Decision of Apple laptops (Macbook) among students working at the University of 17 August 1945 Surabaya. This finding provides important insights for manufacturers, marketers, and academics in designing more targeted marketing strategies, while also helping students in making rational and appropriate purchasing decisions.